2018
DOI: 10.1159/000492004
|View full text |Cite
|
Sign up to set email alerts
|

Overnutrition and Scholastic Achievement: Is There a Relationship An 8-Year Follow-Up Study

Abstract: Objective: The aim of this study was to assess the association between overnutrition and scholastic achievement (SA). Methods: A representative and proportional sample of 477 children of the 5th elementary school grade of both genders was randomly chosen during 2010, in the Metropolitan Region of Chile. SA was measured through the 2009 Education Quality Measurement System (SIMCE) tests of language (LSA), mathematics (MSA) and understanding of the natural environment (UNESA). Current nutritional status was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
5
1
Order By: Relevance
“…An earlier study in Chile reported that being overweight was not associated with poorer mathematical and national language proficiencies. 30 Our study did not find the association between being overweight and academic performance either, despite its plausibility.…”
Section: Discussioncontrasting
confidence: 75%
“…An earlier study in Chile reported that being overweight was not associated with poorer mathematical and national language proficiencies. 30 Our study did not find the association between being overweight and academic performance either, despite its plausibility.…”
Section: Discussioncontrasting
confidence: 75%
“…On the one hand poor or unhealthy nutrition can negatively affect children’s health, growth and cognitive performance. On the other hand over nutrition in children can also increase the incidence of various complications such as cardiovascular diseases (CVDs) risk factors and therefore resulting in poor quality of life from a young age [2].…”
Section: Introductionmentioning
confidence: 99%
“…For Z-BMI a negative correlation was found only in LSA of school-age children from 2010 1HSG and some publications show an inverse and significant association between SA and obesity [4346]; nevertheless, other results suggest that obesity is not associated with academic performance [4,5,12,47,48]. Our recent findings in an eight-year follow-up study also show that obesity and SA in the SIMCE and PSU tests, both with nationally coverage in Chile, are not significantly associated [87]. Results also suggest that physical fitness in boys and obesity status in girls could be important factors not only for health status but also for SA, independent of socio-economic and behavioural backgrounds [45].…”
Section: Discussionmentioning
confidence: 48%